Kajian Fasilitas Khusus Lansia pada Bangunan Hunian Sasana Tresna Werdha RIA Pembangunan Jakarta Timur - Lutfah Kamalia Putri; Lia Rosmala Schiffer (Fakultas Teknik - Universitas Bung Karno, 2024)
Panti Sosial Tresna Werdha provides a solution for elderly individuals whose families face financial and non-financial constraints, leaving them without adequate care. As a residential facility for older adults, a nursing home must meet proper housing standards to support daily activities and reduce the risk of accidents, such as falls and slips, often resulting from design flaws or inadequate facilities. This study examines the elderly-friendly facilities implemented in the Sasana Tresna Werdha building and explores how older residents perceive comfort in their living environment. The research employs a qualitative descriptive method, with data analyzed qualitatively. The findings reveal that the facility incorporates various features to enhance comfort and accessibility for elderly residents. These include a centrally located ramp connecting the second and third floors, handrails along staircases and corridors, and strategically positioned staircases on the right, left, and center of the building, all specifically designed to facilitate mobility and improve the well-being of older residents.